Pengaruh Produk, Promosi, Orang, dan Proses terhadap Keputusan Orang Tua dalam memilih SMA Global Islamic Boarding School - Afrinal Afrinal; Saladin Ghalib; Maryono Maryono (JURNAL BISNIS DAN PEMBANGUNAN, 2015)
The objectives of this study are 1) to identify and analyze the influence of product to parent’s decisions in choosing school 2) to identify and analyze the influence of promotion to parent’s decisions in choosing school 3) to identify and analyze the influence of people to parent’s decisions in choosing school 4) to identify and analyze the influence of process to parent’s decisions in choosing school and 5) to identify and analyze the influence of product, promotion, people, and process simultaneously to parent’s decisions in choosing school.The research uses a quantitative approach with a sample of 177 respondents of parents whose children are currently studying in SMA GIBS. This study uses multiple regression analysis model and uses Statistical Packed for Social Science (SPSS) version 16.0 to analyze the data.The results of this study indicate that 1) the product does not significantly influence the parent’s decision in choosing school 2) the promotion significantly influences the parent’s decision in choosing school 3) the people significantly influence the parent’s decision in choosing school 4) the process significantly influences the parent’s decision in choosing school and 5) the product, promotion, people and process simultaneously have significant influence to parent’s decision in choosing school.Keywords: Product, promotion, people, process, and decisions.